Targeting PTPN22 in Arthritis: Molecular Docking and Pharmacokinetic Evaluation of Artemisia vestita Compounds - Shweta V Bhat (International Journal of Bioinformatics and Computational Biology, 2025)
Rheumatoid arthritis (RA) is a long-term autoimmune condition characterized by inflammation of the synovial membrane, commonly resulting in swelling, pain, stiffness, and overall fatigue. Protein tyrosine phosphatase non-receptor type 22 (PTPN22) has been identified as a risk factor linked to various autoimmune diseases, including RA. In the PTPN22 gene, two missense Single nucleotide polymorphisms (SNPs) are associated with autoimmune conditions. The R620W (C1858T, rs247660) variant in exon 14 has been shown to elevate the negative regulation of B and T cell activation. On the other hand, the R263Q (G788A, rs33396649) variant in exon 10 affects enzyme activity by altering a key amino acid. This study explores the potential of the phytochemical compounds from Artemisia vestita, a folklore medicinal plant with anti-inflammatory and antipyretic properties in the treatment of RA using computational tools. PyRx, a virtual screening software was employed to carry out the molecular docking stimulations. The compounds from A. vestita which demonstrated the most favorable binding with PTPN22 were Vulgarin, Thujyl alcohol, iso-3-Thujyl acetate, (+)-alpha-Thujone and Verbenone. These compounds were chosen for further in-silico analysis and were evaluated for drug-like properties based on ADMET parameters, Lipinski’s rule of five and five physiochemical parameters: Bioavailability score, GI absorption, PAINS and Brenk alerts and solubility. The compound Vulgarin exhibited the best affinity toward PTPN22. Hence, the molecular interaction between PTPN22 and Vulgarin was visualized in DS BIOVIA Discovery Studio Visualizer.
Keywords: Artemisia vestita; in silico analysis; molecular docking; protein tyrosine phosphatase non-receptor type 22(PTPN22); rheumatoid arthritis